Synthesis and characterization of tungsten oxide–cerium oxide/chitosan nanocomposites for photocatalytic degradation of methylene blue in sewage water under sunlight - Dhivya Viswanathan; Surya Parthasarathy; Sutha Sadhasivam; Krishna Prakash Arunachalam; Khuloud A. Alibrahim; Abdullah N. Alodhayb; Saravanan Pandiaraj; Rajakumar Govindasamy; Sridevi Balu (Results in Engineering)
The research examines the implementation of CeO₂, CeO₂/WO₃, and CH/CeO₂/WO₃ hybrid nanocomposites developed through precipitation procedures for the photocatalytic degradation of methylene blue (MB) under sunlight illumination. The crystallographic and functional group analysis of the as-developed nanoparticles was performed through X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR), indicating the presence of the phase-pure nanocomposites with specific functional properties. The surface microstructure of the as-prepared nanoparticles was analyzed through scanning electron microscopy (SEM) analysis. Furthermore, the UV–Visible diffuse reflectance spectroscopy (UV–Vis DRS) reveals that the developed nanocomposite indicates enhanced potential light absorption capability. The antibacterial analysis performed against gram positive and gram-negative bacterial strains such as Escherichia coli and S. aureus indicates that the prepared CH/CeO₂/WO₃ hybrid nanocomposites exhibit remarkable bacterial resistance. Finally, the MB dye degradation of against the CH/CeO2/WO3 hybrid nanocomposite exhibit better dye decomposition. Additionally, the dye degradation research demonstrates that the produced CH/CeO2/WO3 hybrid nanocomposite exhibits significant dye decomposition and is extremely active in acidic media. Additionally, the stability and recyclability of the fabricated nanocomposite was assessed, and it demonstrated that slight decrease in nanocomposite effectiveness occurred during five consecutive cycles of effluent decomposition.